2013
DOI: 10.1111/cen.12225
|View full text |Cite
|
Sign up to set email alerts
|

High sodium intake is associated with increased glucocorticoid production, insulin resistance and metabolic syndrome

Abstract: High sodium diet was associated with increased urinary cortisol and its metabolites. Also, HS diet was associated with HT, insulin resistance, dyslipidaemia and hypoadiponectinaemia, even when adjusting by confounding variables. Further, we observed that high salt intake, IR and higher cortisol metabolites, alone or combined in a clinical simple model, accurately predicted MetS status, suggesting an additive mechanism in obesity-related metabolic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
128
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(146 citation statements)
references
References 37 publications
13
128
2
3
Order By: Relevance
“…However, Baudrand et al (24) reported that there is no statistical difference in BMI between participants with high Na intake and adequate Na intake (29·4 v. 29·0 kg/m 2 ). In addition, the current study observed that participants with obesity had higher Na excretion than those without.…”
Section: Discussionmentioning
confidence: 97%
“…However, Baudrand et al (24) reported that there is no statistical difference in BMI between participants with high Na intake and adequate Na intake (29·4 v. 29·0 kg/m 2 ). In addition, the current study observed that participants with obesity had higher Na excretion than those without.…”
Section: Discussionmentioning
confidence: 97%
“…HSD-induced insulin resistance (IR) was found to be driven by impaired microvascular responsiveness to insulin [52] and linked with decreased insulin sensitivity, phosphatidylinositol (PI) 3-kinase or Akt activation [53], and AT hypoxia [54]. Further study indicated that HSD and IR, alone or combined, might have a strong relationship with obesity-related metabolic disorders [55]. Studies showed that high salt intake increased serum gastrin levels relative to an LSD in the Chinese subjects [56], and gastrin is a critical hormonal regulator that is known to induce gastric secretion, stimulate pancreatic secretion, and increase blood circulation and water secretion in the stomach and intestine.…”
Section: Hsd and Gi Hormonesmentioning
confidence: 99%
“…In this regard, low water intake predicts development of insulin resistance, 106 whereas increasing water intake is associated with weight loss, at least in overweight subjects. 107 High salt intake is also associated with obesity, metabolic syndrome, and diabetes [108][109][110][111][112] and predicts these conditions independent of energy intake or intake of sugary beverages. [112][113][114] Thus, the development of obesity is not simply because of greater intake of soft drinks consequent to salt-induced thirst, which has been suggested.…”
Section: Ckdmentioning
confidence: 99%